For or against gender equality? Evaluating the post-cold war 'Rule of Law' reforms in Sub-Saharan Africa - Celestine Nyamu-Musembi (United Nations Research Institute for Social Development (UNRISD), 2005)
The central question explored in this paper is: has the post-Cold-War rule of law (ROL) reform agenda in sub-Saharan Africa enhanced or impeded gender equality? Rule of law (ROL) reforms are seen as indispensable to establishing a market economy and democratic rule, the two prongs of the neo-liberal project. In sub-Saharan Africa, legal and institutional reforms that originated with the 'second wave' of political reform in the immediate post-Cold-War era have been justified in terms of these twin goals. The overwhelming emphasis and investment has been in creating a suitable legal and institutional environment for the market. Some attention has been given to the democratic-rule prong, for instance through reform of electoral laws and of institutional structures such as courts and national human rights commissions. The bulk of substantive legal reforms have focused on areas such as commercial codes, bankruptcy, banking, tax and property laws (including intellectual property), corporate governance and freedom of information. In this same period, the region has seen a significant rise in the profile and impact of movements concerned with gender equality. Some of the concerns of the gender equality movement do overlap with the ROL agenda. Examples include ending the vicious effects of corruption, ineptitude and institutionalized bias (including gender bias) in the functioning of institutions that administer justice; and progressive constitutional reforms that have the potential to enhance legal protection from gender-based discrimination. However, a juxtaposition of the law reform priorities with the priorities articulated by gender equality advocates shows that ROL reforms have not automatically translated into reforms that enhance gender equality. The gains for gender equality have been limited and hard won. A large part of the gender equality agenda remains unaddressed by the legal and institutional reforms undertaken so far. The main gaps identified are: Constitutional guarantees of rights have only a limited reach, particularly where customary and religious laws are not only allowed to regulate family matters but to supersede anti-discrimination laws. Reforms to property law have at worst deepened gender inequality and at best left existing biases intact. Official discussion of gender and land tenure remains disconnected from broader processes of economic restructuring, such as those affecting the financial services industry. Financial sector reforms have not been co-ordinated with reform of land and family legislation and practice, yet land and family law are at the heart of women's ability to access financial services...
Keywords: 330